2017
DOI: 10.1021/acs.iecr.7b02719
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Transformation of Waste Bone Oil into High Quality Biodiesel via a Synergistic Catalysis of Porous Organic Polymer Solid Acid and Porous γ-Al2O3-K2O Solid Base

Abstract: We report here a novel synergistic catalysis system combined with porous organic polymeric solid acid (H-PDVB-SO 3 H) and K 2 O doped porous γ-Al 2 O 3 solid base (γ-Al 2 O 3 -K 2 O). H-PDVB-SO 3 H and γ-Al 2 O 3 -K 2 O have abundant nanopores, controllable surface wettability, and high concentrations of acidic and basic sites. The synergistic catalysis system exploited by us could efficiently transform acidulated bone oil and plant oil into high quality biodiesel under mild conditions, which achieved ASTM spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…As displayed in Figure 2, all samples show type‐IV isotherms with large adsorption amount at higher relative pressure range of 0.88∼1.0, which indicates the ample presence of meso‐macroporous structures in those of samples [38–46] . Moreover, wide distribution ranging from 0 to 50 nm was found all the 3D‐NHPC‐x samples, confirming the formation of hierarchical nanopores in 3D‐NHPC‐x [47–55] . The textural parameters in Table 1 show that the 3D‐NHPC‐x are large in BET surface areas (479∼753 m 2 /g) and total pore volumes (2.23∼2.85 cm 3 /g).…”
Section: Resultsmentioning
confidence: 73%
“…As displayed in Figure 2, all samples show type‐IV isotherms with large adsorption amount at higher relative pressure range of 0.88∼1.0, which indicates the ample presence of meso‐macroporous structures in those of samples [38–46] . Moreover, wide distribution ranging from 0 to 50 nm was found all the 3D‐NHPC‐x samples, confirming the formation of hierarchical nanopores in 3D‐NHPC‐x [47–55] . The textural parameters in Table 1 show that the 3D‐NHPC‐x are large in BET surface areas (479∼753 m 2 /g) and total pore volumes (2.23∼2.85 cm 3 /g).…”
Section: Resultsmentioning
confidence: 73%
“…However, Liu et al investigated key physicochemical properties of polydivinylbenzene-based polymer acid catalyst for biodiesel synthesis in-depth, especially with focus on the catalyst dilatability, hydrophobicity, and oleophilicity (Table , entries 5–8). Hydrothermal polymerization was carried out using DVB as a monomer, azobis­(isobutyronitrile) (AIBN) as initiator, and THF/H 2 O as a solvent, which could give a swelling mesoporous PDVB polymeric precursor. After sulfonation with different amounts of chlorosulfonic acid (ClSO 3 H) in CH 2 Cl 2 , solid polymer acid catalysts (PDVB- x -SO 3 Hs) bearing organic framework were obtained from PDVB and found to exhibit large surface area (280–380 m 2 /g), affluent mesoporosity, and high -SO 3 H concentration­(3.9–4.1 mmol/g).…”
Section: Chemosynthetic Organic Polymersmentioning
confidence: 99%
“…From a practical point of view, Liu et al reported a novel synergistic catalysis process by coupling organic polymer acid (H-PDVB-SO 3 H) with K 2 O-doped porous γ-Al 2 O 3 solid base (γ-Al 2 O 3 -K 2 O) for biodiesel production using waste acidulated bone oil as raw feedstock. Combo H-PDVB-SO 3 H and γ-Al 2 O 3 -K 2 O-mediated catalytic system is effective and economic for converting waste oils into high-quality biodiesel, in view of its commendable reaction activity and satisfying recyclability, to some extent . Although the aforementioned catalysts performed well in both processes of esterification and transesterification, several extremely dangerous reagents such as ClSO 3 H need to be used for the polymeric catalyst preparation.…”
Section: Chemosynthetic Organic Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooking oil-based biodegradable-polymer films have attracted the curiosity of many people owing to their capacity to replace traditional petrochemical products in a variety of ways [32]. Epoxidized fatty acid methyl esters (E-FAME) are the essential raw material that may be utilized as an additional plasticizer for polyvinyl chloride (PVC) [33][34][35]. Potential plasticizers included cyclohexane tricarboxylic acid triesters produced from vegetable oil, which demonstrated good compatibility with PVC and, in some cases, even better compatibility than DEHP [36].…”
Section: Introductionmentioning
confidence: 99%